1989
DOI: 10.1152/jappl.1989.67.1.116
|View full text |Cite
|
Sign up to set email alerts
|

Adenine nucleotide degradation in human skeletal muscle during prolonged exercise

Abstract: Eight healthy men cycled at a work load corresponding to approximately 70% of maximal O2 uptake (VO2max) to fatigue (exercise I). Exercise to fatigue at the same work load was repeated after 75 min of rest (exercise II). Exercise duration averaged 65 and 21 min for exercise I and II, respectively. Muscle (quadriceps femoris) content of glycogen decreased from 492 +/- 27 to 92 +/- 20 (SE) mmol/kg dry wt and from 148 +/- 17 to 56 +/- 17 (SE) mmol/kg dry wt during exercise I and II, respectively. Muscle and blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(81 citation statements)
references
References 0 publications
7
72
2
Order By: Relevance
“…These findings are consistent with studies on exhausted skeletal muscles (45). Although undetected in the present study, purine metabolism generates ammonia, which is a known muscle fatigue factor (46). Therefore, the depletion of energy sources and accumulation of inhibitors of muscle contraction (e.g., ammonia) are factors for muscle fatigue (failure of muscle contraction).…”
Section: Biochemical Insight Into the Development Of Exhaustion And Csupporting
confidence: 93%
“…These findings are consistent with studies on exhausted skeletal muscles (45). Although undetected in the present study, purine metabolism generates ammonia, which is a known muscle fatigue factor (46). Therefore, the depletion of energy sources and accumulation of inhibitors of muscle contraction (e.g., ammonia) are factors for muscle fatigue (failure of muscle contraction).…”
Section: Biochemical Insight Into the Development Of Exhaustion And Csupporting
confidence: 93%
“…No reductions in either of these highenergy phosphagen compounds were evident in freeze-dried tissue, either in the mixed homogenate or in specific fibre types. In the case of ATP, several previous studies have either demonstrated no change (Norman et al 1987) or a reduction in ATP (Broberg & Sahlin, 1989;Green et al 1989) in freeze-dried tissue of mixed fibre types during two-legged cycling at intensities comparable or moderately higher than employed in this study. In the one study published examining ATP levels in type I and type II fibres following 60 min of exercise at 70% V02 max, no change in ATP concentration was evident in either fibre type (Norman et al 1987).…”
Section: Discussioncontrasting
confidence: 53%
“…An additional and important objective of this study was to examine the timedependent change in energy status in type I and type II fibres because of the assertion that glycogen depletion in contracting muscle cells is accompanied by a reduction in the rate of ATP resynthesis (Broberg & Sahlin, 1989). Consequently, reductions in ATP concentration were expected, particularly late in exercise and in type I fibres where a large percentage of the fibres had low or very low concentrations of glycogen.…”
Section: Discussionmentioning
confidence: 99%
“…All of these scenarios are associated with a significant increase in muscle adenine nucleotide loss during exercise (21)(22)(23)25,26) and consequently the development of muscle fatigue (17,18,(25)(26)(27)(28). Based on the emerging likelihood that GPis will be used clinically in the treatment of type 2 diabetes, we felt it important to address the effects of glycogen phosphorylase administration on skeletal muscle energy metabolism and function.…”
mentioning
confidence: 99%